Physiological responses to heat acclimation: A systematic review and meta-analysis of randomized controlled trials - Rahimi, G. R. M.; Albanaqi, A. L.; Van der Touw, T.; Smart, N. A. (Journal of Sports Science & Medicine, 2019)
The aim of this meta-analysis was to evaluate the effectiveness of heat acclimatization (HA) on time trial (TT) performance, maximum oxygen uptake (VO2max), exercise heart rate (HRE), time trials heart rate (HRTT), maximal heart rate (HRM), core temperature (TC), mean skin temperature (TS), thermal comfort (TComf), plasma volume (PV), blood lactate concentration and rate of perceived exertion (RPE). Cochrane-CENTRAL, EMBASE, CINAHL and PubMed databases and reference lists of included studies were searched for randomized controlled trials that investigated the efficacy of HA in athletes. Data were then extracted from the entered studies for analyses. A total of 11 randomised controlled trials (215 participants; mean age, 26.09 years; 91% men) were included after screening of 508 titles and abstracts and 19 full-text articles. The pooled standard mean difference (SMD) between the HA and non-HA groups were 0.50 (95% CI: 0.03 to 0.97, p = 0.04) for TT performance and 1 (95% CI: 1 to 2, p = 0.007) for HRTT. The pooled mean difference (MD) between the HA and non-HA groups were -7 (95% CI: -13 to -1, p = 0.03) for HRM. The changes in TComf and RPE were too small to be meaningful. There were no significant differences between the HA and non-HA groups for VO2max, HRE, TC, TS, PV and blood lactate concentration (all p > 0.05). This meta-analysis implies that HA may improve tolerance to discomfort during heat exposure, but may not necessarily improve the associated physiological markers of improved performance.